Studies of locally Effective Microorganisms (EM) to enhance the degradation of empty fruit bunches, POME & cake during composting process - Kabbashi, Nassereldeen Ahmed; Noruldin, Norzalina; Mirghani, Mohamed Elwathig Saeed (International Islamic University Malaysia, 2013)
Palm oil industry is among the 12 National Key Economic Areas (NKEAs) areas which are at the core of the Economics Transformation Program (ETP). Malaysia's palm oil industry is the fourth largest contributor to the national economy and currently accounts for RM53 billion. Wastes from oil palm industries are generated daily and every year becoming a great concern consequently, an urgent development of bio-composting process has been researched. Bio composting is an environmentally way where its product could be utilized as plant growth enhancement. The study was concerning about simple composting process using substrate that has been selected in this experiment which are EFB, POME and CAKE whereas the co-substrate is sawdust. Phanerochaete chrysosporium was inoculated in compost trays and the growth can be seen clearly in day 15. It is a white fungus that was serves to degrade the lignin of the substrate. At day 15 Tricorderma Viride was inoculated while Aspergillus Niger was inoculated at day 30. Pennicillium was inoculated at day 45 to destroy the toxicity of the compost. Tray bioreactor was used to test the efficiency of composting process by solid state fermentation process. The composting period for this process is 60 days and some parameters are needed to be determined to evaluate the compost quality. The maturity of the composting could be reflected by the best C/N ratio obtained was run 6 which are 16.51, pH, and germination index result of 154%. This simple technology urge to enhance the productivity and sustainability of the Malaysian palm oil milling industry by improving the local isolated fungal strains and increasing composting utilization